An Activity-Oriented Conceptual Framework for Mobile Learning Database Educational Classroom - Trudi Komansilan; Johan Reimon Batmetan; Sondy C Kumajas (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Mobile learning is very helpful in replacing the implementation of online teaching and learning activities during the COVID-19 pandemic. The use of mobile learning will be very helpful in the implementation of teaching and learning activities, especially when using it as a learning medium. This needs to be regulated in a learning framework. We made modifications to the design framework of the m-Learning activity, to describe the Requirements & Constraint Analysis cycle, m-Learning scenario design, technology environment design, learner support services design. We found that the framework still needed additional Learning Outcomes at the beginning of the cycle. This learning achievement is important so that the learning carried out can be measured and evaluated as material in the future. The results of the development of this framework have been successfully implemented in database learning in vocational high schools. We conclude that this framework is very important to be applied to activity-oriented learning using mobile learning so that it can produce optimal learning outcomes.